1990
DOI: 10.1172/jci114839
|View full text |Cite
|
Sign up to set email alerts
|

Chylomicron remnant clearance from the plasma is normal in familial hypercholesterolemic homozygotes with defined receptor defects.

Abstract: The retinyl palmitate fat tolerance test was used to measure chylomicron remnant clearance in 10 normal subjects (apolipoprotein E Iapo El isotypes 3 or 4 only), 6 normolipidemic apo E2/2 homozygotes and 5 familial hypercholesterolemic homozygotes. Skin fibroblasts with fully upregulated LDL receptors from the latter subjects degraded rabbit "25I-jBVLDL in vitro at rates ranging from < 10-48% of normal. Experiments in vivo revealed no significant differences between the normal and homozygous familial hyperchol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
78
4
2

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(89 citation statements)
references
References 35 publications
5
78
4
2
Order By: Relevance
“…Studies involving postprandial lipoprotein remnants with REs as a marker in homozygous or heterozygous FH patients revealed either abnormalities 12,38 or a normal removal of chylomicron remnants. 13,31 We confirmed an earlier report by Castro Cabezas et al 12 that postprandial chylomicron remnants reflected by REs in the SfϽ1000 fraction were elevated in heterozygous FH patients compared with matched control subjects. In the fasting state and the early postprandial period (first 3 hours after a meal), smaller sized chylomicrons (considered to be atherogenic) are secreted.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Studies involving postprandial lipoprotein remnants with REs as a marker in homozygous or heterozygous FH patients revealed either abnormalities 12,38 or a normal removal of chylomicron remnants. 13,31 We confirmed an earlier report by Castro Cabezas et al 12 that postprandial chylomicron remnants reflected by REs in the SfϽ1000 fraction were elevated in heterozygous FH patients compared with matched control subjects. In the fasting state and the early postprandial period (first 3 hours after a meal), smaller sized chylomicrons (considered to be atherogenic) are secreted.…”
Section: Discussionsupporting
confidence: 90%
“…9 -11 Castro Cabezas et al 12 have demonstrated a small but significant postprandial increase in retinyl palmitate concentration in the chylomicron remnant fraction (Svedberg flotation unit [Sf]Ͻ1000) in heterozygous FH patients compared with normolipidemic control subjects. However, Rubinsztein et al 13 did not observe any accumulation of vitamin A-labeled chylomicrons, IDLsized remnants, or chylomicron remnants in homozygous FH patients. Additionally, Kowal et al 14 reported that only 5% of the binding capacity of the LDL receptor was needed to remove chylomicron particles, suggesting only a minor role for the LDL receptor in the removal process of lipoprotein remnants.…”
mentioning
confidence: 90%
“…remnants is controversial, because humans with homozygous familial hypercholesterolaemia (FH) seem to clear chylomicron remnants without any gross abnormality [56]. The Watanabe heritable hyperlipidaemic rabbit (WHHL) is an homozygous FH model which also seems to retain the capacity of clearing intestinal lipoproteins [57].…”
Section: Intravascular Metabolism Of Trlmentioning
confidence: 99%
“…In contrast, Kita et al (1982) found no uptake of abnormal lipoprotein remnants in the Watanabe heritable hyper-lipidaemic rabbit, an animal with dysfunctional LDL receptors. Similarly in humans, the lack of LDL receptors does not lead to a pathological change in the metabolism of dietary fat (Rubinsztein et al, 1990).…”
mentioning
confidence: 97%